Burden of Sliding Scale Insulin Use in Elderly Long‐Term Care Residents with Type 2 Diabetes Mellitus. Issue 12 (25th November 2013) - Pandya, Naushira; Wei, Wenhui; Meyers, Juliana L.; Kilpatrick, Brett S.; Davis, Keith L.
<x xml:space="preserve">Abstract</x> Objectives To examine prevalence, practice patterns, and associated burden of sliding scale insulin (SSI) therapy in elderly adults with type 2 diabetes (T2DM). Design A retrospective cross‐sectional study assessing merged medical chart data and the Minimum Data Set. Setting One hundred seventeen long‐term care (LTC) facilities in seven U.S. states. Participants Elderly adults with insulin‐treated T2DM (N = 2, 096) admitted to a LTC facility after January 1, 2009, who had been in the facility for at least 3 months before chart abstraction and had received treatment with non‐SSI or SSI regimens. The latter were categorized into SSI‐only, basal–SSI, prandial–SSI, basal–prandial–SSI, and multiple regimens with SSI. Data were collected from September 2010 through September 2011. Measurements Demographic and clinical characteristics were recorded. Fingerstick burden was assessed as the average number of fingersticks per week and average number without subsequent insulin administration. Other measures included glycosylated hemoglobin (HbA1c) and hypoglycemia events. Results Overall, 73.8% of participants received SSI therapy. SSI‐treated participants were more likely to be younger (P = .01), non‐white (P = .002), and receiving sulfonylurea (P = .004) than non‐SSI treated participants. SSI therapy was associated with a mean ± standard deviation of 19.9 ± 7.9 fingersticks per week, of which 12.5 ± 7.6 were not followed by insulin administration. Fewer SSI‐treated participants than non‐SSI treated participants had one or more HbA1c measurements of 7.0% or less (48.8% vs 57.2%) or 8.5% or less (85.2% vs 87.6%, respectively). Rates of hypoglycemia were similar in both groups (15.0% vs 14.9%). Conclusion SSI therapy is widely used in LTC facilities and is associated with a high fingerstick burden. SSI regimens are associated with poorer glycemic control but a rate of hypoglycemia similar to that of non‐SSI regimens.